Perfusion of Porcine Kidneys With Macromolecular Heparin Reduces Early Ischemia Reperfusion Injury. Issue 2 (February 2019) - Sedigh, Amir; Nordling, Sofia; Carlsson, Fredrik; Larsson, Erik; Norlin, Bo; Lübenow, Norbert; Lennmyr, Fredrik; Tufveson, Gunnar; Magnusson, Peetra U.; Lorant, Tomas
Abstract : Background: Previously, we have been able to demonstrate the possibility of coating the inner surface of the renal arteries in porcine kidneys with a heparin conjugate during hypothermic machine perfusion (HMP). The purpose of this study was to assess the efficacy of this treatment in reducing early ischemia-reperfusion injury. Method: Brain death was induced in male landrace pigs by stepwise volume expansion of an epidural balloon catheter until negative cerebral perfusion pressure (CPP) was obtained. Both kidneys (matched pairs; n = 6 + 6) were preserved for 20 hours by HMP during which 50 mg heparin conjugate was added to one of the HMP systems (treated group). A customized ex vivo normothermic oxygenated perfusion (NP) system with added exogenous creatinine was used to evaluate early kidney function. Blood, urine and histological samples were collected during the subsequent 3 hours of NP. Results: Kidney weight was lower at the end of NP ( P = 0.017) in the treated group compared with control kidneys. The rate of decline in creatinine level was faster ( P = 0.024), total urinary volume was higher ( P = 0.031), and the level of urine neutrophil gelatinase-associated lipocalin (NGAL) was lower ( P = 0.031) in the treated group. Histologically, less tubular changes were seen ( P = 0.046). During NP intrarenal resistance remained lower ( P < 0.0001) in the treated group. Conclusions: Perfusion of porcine kidneys with heparin conjugate during HMP reduces preservation injury and improves organ function shortly after reperfusion. No increased risk of bleeding was seen in this setup. This protective strategy may potentially improve the quality of transplanted kidneys in the clinical setting. Abstract : The authors demonstrate that perfusion of porcine kidneys with heparin conjugate during hypothermic machine perfusion reduces preservation injury and improves organ function shortly after reperfusion.